2014
DOI: 10.1021/jf502950u
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Biphasic Effects of Resveratrol on Human Natural Killer Cellsin Vitro

Abstract: Resveratrol (RES) is a polyphenol phytoalexin from plants, which has been reported to possess a variety of biological effects. The properties of RES on human natural killer (NK) cells were assessed in this study. Results showed that RES has concentration-dependent biphasic effects on NK cells. In high concentration (50 μM), RES can inhibit viability and promoted apoptosis of NK cells and human lymphoblastoid T (Jurkat) cells, which may affect the caspase signaling pathway. The Jurkat cells were more sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…[421] showed that in vitro exposure to resveratrol produced a biphasic effect on anti-CD3/anti-CD28-induced development of both IFN-γ - IL2- and IL4-producing CD8+ and CD4+ T cells (with stimulation at low resveratrol concentrations and suppression at high concentrations). Similarly, it was found to induce a significant enhancement at low concentrations and suppression at high concentrations of both cytotoxic T lymphocytes and NK cell cytotoxic activity [421], and this biphasic modulation of NK cells has been confirmed in more recent research as well [422]. The administration of low doses of resveratrol also inhibited Renca tumor growth with regulatory T cells being decreased, and a massive amount of activated CD8 + T cells accumulating in the tumor microenvironment.…”
Section: Low Toxicity Approachesmentioning
confidence: 79%
“…[421] showed that in vitro exposure to resveratrol produced a biphasic effect on anti-CD3/anti-CD28-induced development of both IFN-γ - IL2- and IL4-producing CD8+ and CD4+ T cells (with stimulation at low resveratrol concentrations and suppression at high concentrations). Similarly, it was found to induce a significant enhancement at low concentrations and suppression at high concentrations of both cytotoxic T lymphocytes and NK cell cytotoxic activity [421], and this biphasic modulation of NK cells has been confirmed in more recent research as well [422]. The administration of low doses of resveratrol also inhibited Renca tumor growth with regulatory T cells being decreased, and a massive amount of activated CD8 + T cells accumulating in the tumor microenvironment.…”
Section: Low Toxicity Approachesmentioning
confidence: 79%
“…RES concentrations of 25 and 50 µM diminished NK cells cytotoxicity by 29% and 39%, respectively. At 3.13 µM RES was demonstrated to enhance the expression of both TNFγ (by 4.5-fold) and triggering cytotoxicity receptor NKG2D (by 6.4-fold), which might account for the enhanced cytotoxicity of NK cells [59].…”
Section: Resveratrolmentioning
confidence: 94%
“…However, in this study, PO-MSC viability decreased when resveratrol dose was above 10 μM. It seems that the osteogenic effect of resveratrol varies according to dosage or cell types (33)(34)(35)(36)(37). Therefore, further investigation on the optimal dosage and administration method of resveratrol for accelerating osteogenesis of PO-MSC is needed.…”
Section: Discussionmentioning
confidence: 63%